The association between history of appendectomy and gut microbiota composition: a follow-up cross-sectional study - Hadžić, Matija; Hammer, Paul; Krumbiegel, Carsten; Moskalenko, Olga; Karačić, Andrija; Hadžić, Daria (Frontiers in Microbiology, 2026)
IntroductionThe appendix is thought to act as a regulatory immune organ and gut microbiota reservoir. Although appendectomy is linked to health risks, its impact on the gut microbiota remains understudied.MethodsThis study is conceived as a cross-sectional retrospective follow-up study. Three comparisons were performed on gut microbiota data using self-reported metadata retrieved from a European laboratory’s extensive database. First, subjects with (wA) and without (noA) appendectomy during stool sampling were compared. Second, healthy individuals were selected based on specific criteria by comparing those with (HwA) and without (HnoA) appendectomies. Finally, healthy (HwA) and non-healthy (nHwA) subjects with a history of appendectomy were compared. Due to the study design, the timing and cause of the appendectomy were unknown. Data on confounding factors, such as age, BMI, and sex, were analyzed as covariates. Regarding the gut microbiota, alpha and beta diversity, relative abundance of phyla, genera, and metabolic pathways were compared.ResultsSignificant differences were found in the gut microbiota composition and functionality between 2′615 adult subjects who had and 13′103 adults who had not undergone appendectomy (wA vs. noA), but also in confounding factors such as age, sex, and BMI. No significant differences were found in the gut microbiota between the 111 healthy adult subjects and 876 adults who had not undergone appendectomy (HwA vs. HnoA) at the time of stool sampling. Significant differences were found between 111 healthy and 2′504 non-healthy subjects who underwent appendectomy (HwA vs. nHwA). The gut microbiota composition of nHwA differed significantly in beta diversity; it was less diverse (Shannon entropy) and showed a decreased abundance of two genera, Eubacterium ruminantium and Lachnospiraceae FCS020. The HwA group was found to consume additional portions of vegetables and fruits and sleep longer, but these differences were not significant.ConclusionOur study found significant differences in the gut microbiota composition between healthy and non-healthy subjects who underwent appendectomy, but no difference in healthy subjects with or without appendectomy. Further studies are needed to elucidate whether these differences are due to different restorative capacities over time.